EFEKTIVITAS PERUPUK (Phragmites karka) DAN MIKROORGANISME EFEKTIF (EM) DALAM PENGOLAHAN LIMBAH CAIR DOMESTIK RUMAH TANGGA - Muhammad Ricky Saputra; Dini Sofarini; Yunandar Yunandar (EnviroScienteae, 2014)
This research aimed (a) to find out the changes of the value of water quality parameters in domestic household waste by using perupuk (Phragmites karka) and Effective Microorganisms (EM); (b) to prensent the changes in values of water quality parameter; and (c) to compare the value of water quality parameter on phytoremediation, bioremediation and both of combinations. The study was conducted by using 3 treatments, 4 repetitions and 1 control. The data obtained from the research was quantitative data that was processed by One Way Anova analysis with advanced test using LSD and Duncan test with trust level (sig) = 0.05.The results obtained from this study is that in water reservoir the combination of EM4 and Perupuk (Phragmites karka) was the best treatment in this study that have been executed. The combination of two treatments that were able to repair four of the seven water quality parameters are DO (-31.48%), BOD5 (99.57%), COD (99.87%), and TSS (92.41%) from standard of environment quality in Peraturan Pemerintah (PP) No.82 tahun 2001 Kelas II